Основні теоретичні конструкти гендера. - Краснопольська, Т.М.; Краснопольская, Т.М.; Krasnopol'skaja, T (My University, 2012)
The article considers the establishment the concept of "gender" in the light of the formation of various theories and concepts of gender: the theory of social construction of gender, gender as a stratiﬁ cation category, gender as a cultural metaphor. Then reviewed in detail the theory of formation gender roles.
Краснопольська Т.М. Основні теоретичні конструкти гендера. / Т.М.Краснопольська //Актуальні проблеми політики : зб. наук. пр. / гол. ред. С. В. Ківалов ; відп. за вип. Л. І. Кормич. – Одеса : Національний університет "Одеська юридична академія" : Південноукраїнський центр гендерних проблем, 2012. – Вип. 44. – C.236 - 244.
Keywords: Поняття "гендер"; Концепції гендера; Основні теорії формування гендерної ролі; Основные теории формирования гендерной роли; Концепции гендера; Понятие "гендер"; The term "gender"; Concepts of gender; The basic theory of the formation of gender roles